The relationship between carbon dioxide emissions, energy consumption, and GDP: A recent evidence from Pakistan. Issue 1 (31st December 2016) - Mohiuddin, Obaidullah; Asumadu-Sarkodie, Samuel; Obaidullah, Madina
Abstract: In this study an attempt was made to investigate carbon dioxide emissions, energy consumption (EC), GDP, and electricity production from oil, coal and natural gas, a recent evidence from Pakistan by employing a time series data spanning from 1971 to 2013. The study employed the vector error correction model to estimate the long-run equilibrium relationship. There was evidence of long-run equilibrium relationship running from EC, electricity production from coal, electricity production from natural gas, electricity production from oil and GDP to carbon dioxide emissions. The policy implication of the VEC model means that a 1% increase in energy production from oil in Pakistan will increase carbon dioxide emissions by 13.7% in the long-run. There was evidence of a unidirectional causality running from EC to carbon dioxide emissions, electricity production from natural gas to EC, EC to electricity production from oil, electricity production from natural gas to GDP and GDP to electricity production from oil. Evidence from the generalized impulse-response analysis shows that three components contribute to carbon dioxide emissions in Pakistan, which include EC, energy production from gas and GDP.